Bamboo-Based Activated Carbon as Binder-Free Electrode of Supercapacitor Application. (October 2020) - Taer, Erman; Sihombing, Martauli; Taslim, Rika; Agustino,; Apriwandi,
Abstract: Activated carbon has been an ideal material for supercapacitor electrodes. Its extensive used due to abundant, renewable, and cost-effective production. In this work, we developed activated carbon monolith materials through carbonizing bamboo stems wastes and treating them with ZnCl2 in high-temperature pyrolysis as binder-free electrode of supercapacitor application. ZnCl2 impregnation carried out in one-step, two-step, and three-step. Different steps of ZnCl2 impregnation were employed to evaluate the activated carbon preparation variables including one-step, two-step, and three-step. The reduction of monolith dimensions has been reviewed as physical properties. Furthermore, the symmetric supercapacitor was performed with cyclic voltammetry in sandwich-type at 1 M H2 SO4 . In addition, the thicknesses of electrode carbon monoliths were varied such as 0.1 mm, 0.2 mm, and 0.3 mm. The one-step ZnCl2 impregnation in 0.1 mm thickness of carbon monolith were exhibit best electrochemical performance with highest specific capacitance of 145 F g −1 and followed by two-step and three-step impregnation as high as 132 F g −1 and 131 F g −1 in low scan rate of 1 mV s −1, respectively. These results demonstrate that the bamboo stem-based activated carbon monolith materials are promising as binder-free electrode for supercapacitor energy storage.